2022
DOI: 10.1136/bmjgh-2021-007714
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and catastrophic health expenditure among patients with diabetes in China: a nationwide population-based study

Abstract: IntroductionMultimorbidity is common among patients with diabetes and can lead to catastrophic health expenditure (CHE) for their families. This study aims to investigate the prevalence of multimorbidity and CHE among people with diabetes in China, and the association between multimorbidity and CHE and whether this is influenced by socioeconomic status and health insurance type.MethodsA national survey was conducted in China in 2013 that included 8471 people aged ≥18 years who were living with diabetes. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 38 publications
2
28
1
Order By: Relevance
“…In this study, we found that 31.5% (≥40% OOP in CTP) to 45.6% (≥10% OOP in THE) households of old people (≥60 years) living with multimorbidity incurred CHE. This is lower than the CHE incidence (56.6%) revealed in another national representative study for households with diabetic patients with multimorbidity (23), even when our study participants were restricted to those with diabetes. The different results are a reflection of varied thresholds adopted: a more relaxed threshold (≥20% OOP in CTP) was adopted in the above-cited study.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In this study, we found that 31.5% (≥40% OOP in CTP) to 45.6% (≥10% OOP in THE) households of old people (≥60 years) living with multimorbidity incurred CHE. This is lower than the CHE incidence (56.6%) revealed in another national representative study for households with diabetic patients with multimorbidity (23), even when our study participants were restricted to those with diabetes. The different results are a reflection of varied thresholds adopted: a more relaxed threshold (≥20% OOP in CTP) was adopted in the above-cited study.…”
Section: Discussioncontrasting
confidence: 69%
“…Catastrophic health expenditure (CHE) threatens the ability of the household to purchase other goods and services, potentially driving the household into poverty ( 21 , 22 ). Previous studies have shown that even in the wealthy households with health insurance coverage, multimorbidity is significantly associated with the occurrence of CHE ( 12 , 23 ). According to the WHO, global health spending is rising rapidly, and this trend is particularly profound in the low- and middle-income countries (LMICs) ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Razak et al [ 32 ] revealed that the prevalence of BMI lower than 16 kg/m 2 was associated with poverty and low education levels, and this prevalence did not increase over time in most countries studied. Since lower BMI is relevant to poverty and, furthermore, linked to poverty-related diseases [ 33 ], the association of poverty and health, as well as lower socioeconomic level with risk of CHE is widely verified [ 7 , 8 , 9 ], and it cannot be difficult to understand that underweight BMI is related to higher incidence of CHE.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [ 5 ] found that after adjusting for sociodemographic confounders, physical multimorbidity was significantly associated with an increased number of outpatient visits (odds ratio = 1.29, 95% confident interval (CI): 1.27–1.31), inpatient days spent (odds ratio = 1.38, 95%CI: 1.35–1.41), and likelihood of CHE (odds ratio = 1.29, 95%CI: 1.26–1.32). As for economic factors, a series of studies revealed that families with lower socioeconomic status, such as lower family income, lower education level, and higher unemployment, were more likely to incur CHE [ 7 , 8 , 9 ]. Therefore, in order to eliminate CHE and move to UHC, one of the key points is finding ways to light the heavy health-economic burden.…”
Section: Introductionmentioning
confidence: 99%